2014
DOI: 10.1002/oa.2407
|View full text |Cite
|
Sign up to set email alerts
|

New Equations for the Size Reconstruction of Sturgeon from Isolated Cranial and Pectoral Girdle Bones

Abstract: Measurements on cranial and pectoral girdle bones of 56 museum specimens of modern sturgeon (Acipenser sturio and A. oxyrinchus) were used for the establishment of regression equations allowing back‐calculation of size from isolated sturgeon remains. Different curve fittings (power, linear, logarithmic and exponential fit) were modeled to retain the most accurate regression. These were then applied to archaeological sturgeon remains (A. sturio/A. oxyrinchus) from Vlaardingen, a Dutch late Neolithic settlement.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…In Fish Remains in Archaeology and Paleo-Environmental Studies, Casteel (1976) demonstrated the significance of archaeological fish bone analysis, addressing seasonality, morphometric studies, subsistence reconstructions, and fish mortality profiles (i.e., age of fish when captured). Casteel influenced the development of archaeological fish bone analysis worldwide (e.g., Thieren and Van Neer 2014;Zohar et al 2008), but these analyses occurred earlier in America and Europe than in the Pacific Islands. Gifford (1951) reported the first study of prehistoric diet using fish bone from Fiji archaeological sites, with taxonomic identifications by the ichthyologist Fowler (1955).…”
Section: New Directions In Pacific Archaeology: Fish Bone Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In Fish Remains in Archaeology and Paleo-Environmental Studies, Casteel (1976) demonstrated the significance of archaeological fish bone analysis, addressing seasonality, morphometric studies, subsistence reconstructions, and fish mortality profiles (i.e., age of fish when captured). Casteel influenced the development of archaeological fish bone analysis worldwide (e.g., Thieren and Van Neer 2014;Zohar et al 2008), but these analyses occurred earlier in America and Europe than in the Pacific Islands. Gifford (1951) reported the first study of prehistoric diet using fish bone from Fiji archaeological sites, with taxonomic identifications by the ichthyologist Fowler (1955).…”
Section: New Directions In Pacific Archaeology: Fish Bone Analysismentioning
confidence: 99%
“…Fishing studies outside the Pacific Islands still identify a greater range of the so-called cranial elements-e.g., elements of the neurocranium, hyopalatine arch, opercular series, infraorbital series (Amundsen et al 2005;Desse-Berset and Desse 1994;Thieren and Van Neer 2014).…”
Section: Element Selectionmentioning
confidence: 99%
“…In a second step, the total lengths ( L T ) of the fish were reconstructed, as this proved to be an influential factor for the surface pattern of the dermal bones. While the dermal bones of the head and pectoral girdle provide the most accurate fish‐length reconstruction, using the Thieren & Van Neer () regression equations, the scutes, although numerically dominant in archaeological samples, have the disadvantage of being less precise for fish‐length reconstructions. Despite the wide variation in shape and size among scutes within one row, it remains difficult to establish the exact rank of scutes within a row in the case of isolated finds from archaeological sites.…”
Section: Methodsmentioning
confidence: 99%
“…For 30 of the 34 genetically identified specimens, we were able to establish whether the fish was smaller or larger than 1 m TL ( Table 5). The back-calculated lengths, based on models in Thieren and Van Neer (2016), of 18 bones of the head or the pectoral girdle, ranged between approx. 1 and 2 m. In the case of 12 isolated scutes, a rather crude size Table 3 Taxonomic identification of Acipenser sturio (stur) and A. oxyrinchus (oxy) museum specimens from Chassaing et al (2013) and this study.…”
Section: Archaeological Samplesmentioning
confidence: 99%